Novel inhibitors of a Grb2 SH3C domain interaction identified by a virtual screen - Simister, P; Luccarelli, J; Thompson, S; Appella, D; Feller, S; Hamilton, A (2013)
The adaptor protein Grb2 links cell-surface receptors, such as Her2, to the multisite docking proteins Gab1 and 2, leading to cell growth and proliferation in breast and other cancers. Gab2 interacts with the C-terminal SH3 domain (SH3C) of Grb2 through atypical RxxK motifs within polyproline II or 3 10 helices. A virtual screen was conducted for putative binders of the Grb2 SH3C domain. Of the top hits, 34 were validated experimentally by surface plasmon resonance spectroscopy and isothermal titration calorimetry. A subset of these molecules was found to inhibit the Grb2-Gab2 interaction in a competition assay, with moderate to low affinities (5: IC50 320 μM). The most promising binders were based on a dihydro-s-triazine scaffold, and are the first small molecules reported to target the Grb2 SH3C protein-interaction surface. © 2013 Elsevier Ltd. All rights reserved.